Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/13548506.2013.793367
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of same-sex behavior by young Chinese migrant men: context and correlates

Abstract: The purpose of the study is to explore the disclosure of same-sex behavior by men who have sex with men (MSM) to different groups of people (i.e. family, friends, coworkers, and doctors) and the associated sociodemographic, behavioral, and psychosocial factors. A self-administered survey was conducted among 307 migrant MSM, aged 18-30, in Beijing in 2009. Most MSM disclosed their same-sex behavior to friends (69%), followed by family (25%), coworkers (25%), and doctors (24%). Factors associated with disclosure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 13 publications
3
26
1
Order By: Relevance
“…We found that only one-sixth of Chinese MSM had ever disclosed their sexual orientation to a doctor or other healthcare professional. This disclosure rate is slightly lower than clinic-based data findings from Beijing [22], and similar data from other low-and middle-income countries is not available [2,23]. In comparison, this rate is much higher in high-income countries, where local environments are more receptive to MSM life.…”
Section: Discussioncontrasting
confidence: 46%
“…We found that only one-sixth of Chinese MSM had ever disclosed their sexual orientation to a doctor or other healthcare professional. This disclosure rate is slightly lower than clinic-based data findings from Beijing [22], and similar data from other low-and middle-income countries is not available [2,23]. In comparison, this rate is much higher in high-income countries, where local environments are more receptive to MSM life.…”
Section: Discussioncontrasting
confidence: 46%
“…An early research study conducted by Hays et al, indicated that gay men were more likely to disclose to their partners and close friends than to family members [38]. Similarly, other research showed similar findings that gay men, regardless of ethnic cultures or living in different countries, were less likely to disclose to their parents and other family members and instead were more likely to disclose to friends [33,35,[39][40][41]. This could possibility indicate that most gay men sought emotional and social support from their friends within their own gay culture because they were more likely to find acceptance of their sexual orientation and identity as compared with their families.…”
Section: Culturesupporting
confidence: 55%
“…Third, the population of young migrant men is growing and they are more inclined to engage in harmful drinking (Li et al, 2014). Furthermore, a majority of MSM in Beijing consists of young migrants (Guo et al, 2014). As more migrants relocate to large Chinese cities, this may contribute to increasing prevalence of alcohol use and misuse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MSM between the ages of 24 and 35 were more likely to use and misuse alcohol. We speculate that this age group might represent both financially independent and sexually/socially active MSM with greater exposure to alcohol use venues (Guo et al, 2014). A higher likelihood of hazardous and binge drinking was also seen among migrant MSM and those originating from township/village residence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation